2007
DOI: 10.1051/forest:2007040
|View full text |Cite
|
Sign up to set email alerts
|

End-use related physical and mechanical properties of selected fast-growing poplar hybrids (Populus trichocarpa × P. deltoides)

Abstract: -This study focused on physical and mechanical properties of fast-growing poplar clones in relation to potential end uses with high added value. A total of 14 trees from three different clones, all P. trichocarpa × deltoides (T×D) hybrids, were felled in a poplar plantation in Lille (Belgium): six 'Beaupré', four 'Hazendans' and four 'Hoogvorst'. Growth rate was found to have no significant influence on the physical mechanical properties. Although the investigated clones are genetically closely related, import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 11 publications
6
14
0
Order By: Relevance
“…Clones with denser wood generally showed higher mechanical properties (Table 4). This result is in good agreement with previous reports (Bendtsen et al 1981;Hernández et al 1998;Kretschmann et al 1999;De Boever et al 2007). In contrast, Mátyás and Peszlen (1997) did not detect significant clonal effects for strength properties of poplar clones.…”
Section: Clonal Variationsupporting
confidence: 93%
See 1 more Smart Citation
“…Clones with denser wood generally showed higher mechanical properties (Table 4). This result is in good agreement with previous reports (Bendtsen et al 1981;Hernández et al 1998;Kretschmann et al 1999;De Boever et al 2007). In contrast, Mátyás and Peszlen (1997) did not detect significant clonal effects for strength properties of poplar clones.…”
Section: Clonal Variationsupporting
confidence: 93%
“…The overall MOE of the clones studied was comparable to or higher than previous results (Mátyás and Peszlen 1997;Kretschmann et al 1999;De Boever et al 2007). On the other hand, the overall MOR of clones was higher than previous results (Kretschmann et al 1999;De Boever et al 2007). Based on multiple comparisons, clone-4813 and clone-3565 showed higher flexural strength properties among all studied clones (Table 4).…”
Section: Clonal Variationsupporting
confidence: 87%
“…Previous studies have found highly significant relationships between density and mechanical properties in hybrid poplar clones [56,57]. At the individual tree level, density showed a highly significant correlation with flexural MOR and ultimate crushing strength and a moderate but significant correlation with flexural MOE.…”
Section: Phenotypic Correlations Between Wood Propertiesmentioning
confidence: 73%
“…(Bendtsen and Senft 1986;Roos et al 1990). Similarly, Peszlen (1998) found mechanical properties tended to increase from the pith to the bark and De Boever et al (2007) observed changes in MOE, MOR, and density with tree height in hybrid poplar that they attributed to changes in the ratio of heartwood to tension wood. Koubaa et al (1998b) found that tangential and volumetric shrinkage tended to increase from pith to bark in hybrid poplar and that clones varied significantly in wood shrinkage properties but variation between trees of the same clone, while statistically significant, accounted for less than 5% of the variation in shrinkage.…”
Section: Introductionmentioning
confidence: 93%